Effective snow removal devices for road pavement using geothermal heat pipe - Lim, Hyunmuk; Lee, Seokjin; Lee, Jungho (Applied Thermal Engineering, 2025)
Snowfall can significantly reduce road functionality, making removal and de-icing essential for public safety. This study suggests geothermal heat pipes as a sustainable and eco-friendly method for snow removal. A newly designed geothermal heat pipe was experimentally and numerically evaluated for its snow removal performance using a stainless steel container with acetone. The lab-scale heat pipe, with an evaporator length of 660 mm and a condenser length of 200 mm, demonstrated a thermal resistance of 0.08 K/W at the underground temperature of 15 °C. The numerical simulations involved 72 cases with varying installation parameters of full-scale geothermal heat pipes. Results indicated the trends of the thermal performances for snow removal, and this optimal installation design is achieved when heat pipes are installed close to the road pavement surface, with narrow spacing between pipes and proper insulation to minimize heat loss. Also, this study evaluated the effectiveness of geothermal heat pipes for snow removal based on 20 years of meteorological data from Seoul, Republic of Korea. This research provides valuable guidelines for designing and implementing geothermal snow removal devices for resilient road infrastructure, contributing to environmentally friendly and efficient snow management practices.
Keywords: Eco-friendly; Energy; Pavement surface; Public safety; Removal performance; Road pavements; Snow removal; Thermal; Thermal Performance; Underground temperature; Geothermal energy; Heat pipe; Road pavement; Snow removal; Thermal resistance